New Plants for Florida: Pine - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
The Cooperative Forest Genetics Research Program (CFGRP), founded in 1953 by geneticists Tom Perry and Ray Goddard, is a cooperative organization composed of FAES scientists working together with private industries and state agencies to develop genetically improved varieties of slash pine (Pinus elliottii), loblolly pine (P. taeda), longleaf pine (P. palustris) and sand pine (P. clausa). Through faster growth and greater disease resistance, plantations of improved southern pine yield up to 45 percent more usable wood per acre at harvest than the unimproved plantations. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.